The International Negotiation Game: Some Evidence from the Tokyo Round - Chan, Kenneth S. (The Review of Economics and Statistics, 1985)
This paper examines the Tokyo Round negotiation (1973-1979) under various cooperative game solution concepts. Out of the many tariff-cutting proposals in the Tokyo Round, the Swiss proposal was finally agreed upon by all major players. The choice of the Swiss proposal suggested that egalitarian considerations are important for this type of cooperative game. Since the Kalai-Smorodinsky solution, the Shapley value (modified) and the nucleolus solution have this egalitarian property, they all predict the outcome of the negotiation very well. THIS paper investigates the types of cooperative game solution concepts that best describe the tariff reduction negotiations in the Tokyo Round (1973-1979). Since the objective is to infer the type of game that can closely model the actual negotiation, the best game concept for our purposes is the one which predicts the actual outcome (the Swiss tariff-cutting formula) most successfully under periodic resurgence of protectionist ideology as occurred during the Tokyo Round negotiations. There are various cooperative solution concepts: Some emphasize the egalitarian nature of the outcome, some the efficiency nature of the outcome and some emphasize both aspects (see section II). The present paper concludes that when the change in a country's trade balance becomes an important consideration for negotiators, the egalitarian aspect emerges as the most important cooperative game solution concepts. An interesting finding of the present paper is the bargaining powers of the four major players (United States, EEC, Japan, and Canada) were roughly equal. As shall be explained, this is because each of these players was equally destructive to the Tokyo Round negotiation. There are currently four simulation studies on the impacts of the Tokyo Round (Deardorff and Stern (1983), Baldwin et al. (1980), Brown and Whalley (1980), and Cline et al. (1978)). The present paper uses the simulation studies by Cline et al. for our analysis for three reasons: (1) The Brookings study is based on Keynesian short-run impacts of the Tokyo Round, which seems to fit the objectives of negotiators; (2) it represents the most complete welfare analysis of various proposals; and (3) it was the most influential study done around that time; perhaps it can reflect the conventional wisdom of negotiators in that period.' The present paper is organized as follows: Section I discusses the basic assumptions. Section II examines various game solution schemes or concepts. Section III presents the case of the five major proposals. Section IV extends the result of section III to twelve proposals. Section V discusses the robustness of various assumptions followed by a conclusion in section VI.